2012
DOI: 10.5902/198050985729
|View full text |Cite
|
Sign up to set email alerts
|

Alometria e arquitetura de <i>Copaifera langsdorffii</i> (Desf.) Kuntze (Fabaceae) em fitofisionomias neotropicais no sul de minas gerais

Abstract: RESUMOO objetivo deste trabalho foi analisar padrões alométricos e feições arquiteturais de Copaifera langsdorffii em diferentes fisionomias de uma região de tensão ecológica. As fisionomias de floresta, corredor, cerrado e cerrado rupestre foram estudadas nos municípios de Lavras e Carrancas, sul de Minas Gerais, Brasil. Foram estudadas as relações entre diâmetro do tronco, altura, área da copa, grau de deflexão e deslocamento relativo da copa, sendo analisado o grau de semelhança, entre as fisionomias, por m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
0
6
0
5
Order By: Relevance
“…In conditions in which all plants with DBH ≥ 5 cm were considered, such as in the present study, errors are usually high (Table 1), mainly due to the variability of the tree architecture, as observed by Hálle (2010) and Costa et al (2012). However, other aspects were identified, such as the occurrence of broken canopies and the presence of hollow boles or boles attacked by fungi that reduce the basic specific mass (weight) of the bole wood.…”
Section: Discussionmentioning
confidence: 58%
“…In conditions in which all plants with DBH ≥ 5 cm were considered, such as in the present study, errors are usually high (Table 1), mainly due to the variability of the tree architecture, as observed by Hálle (2010) and Costa et al (2012). However, other aspects were identified, such as the occurrence of broken canopies and the presence of hollow boles or boles attacked by fungi that reduce the basic specific mass (weight) of the bole wood.…”
Section: Discussionmentioning
confidence: 58%
“…According to Thorpe et al (2010), competition for canopy space is a fundamental structuring feature of forest ecosystems, and the result of this competition determines the size of the canopy of each tree, which reflects in interception of light, photosynthetic capacity, growth and even survival. Costa et al (2012) observed that increasing the density of tree vegetation contributed to increase competition of the canopy for light. Siqueira (2006), verified that competition of the crown by light favors the development of the higher branches in detriment of the lower ones.…”
Section: Resultsmentioning
confidence: 99%
“…Siqueira (2006), verified that competition of the crown by light favors the development of the higher branches in detriment of the lower ones. On the other hand, Costa et al (2012) observed that the decrease of the density of the tree vegetation facilitated the penetration of light, making possible the existence of lower live branches. Costa and Finger (2016), found that in a natural subtropical forest, the decrease of the competition favors the increase of the crown length of Araucaria angustifolia.…”
Section: Resultsmentioning
confidence: 99%
“…With great ecological plasticity, the species can occurs naturally in entire Brazilian territory, as in region of Minas Gerais state, Cerrado, Caatinga, Atlantic Forest, Riparian Forest formations and associated ecosystems (CARVALHO et al, 2009;MELO JUNIOR, CECCANTINI and BONA, 2011;COSTA et al, 2012b;NUNES et al, 2015;CARVALHO et al, 2018). According Orellana and Koehler (2008), although wood is the main economic resource derived from forests, some species have great importance for alternative products supply, as in the case of oil-resin, with wide range of medical applications (PIERI, MUSSI and MOREIRA, 2009;MUSSI et al, 2009;HECK, VIANA and VICENTINI,2012).…”
Section: Introductionmentioning
confidence: 99%